From Bengal to the Cape : Bengali slaves in South Africa from 17th to 19th century - Datta, Ansu, 1928- ([United States?] : Xlibris Corporation, 2013)
"In From Bengal to the Cape, Professor Ansu Datta opens up a hitherto little researched topic of transoceanic slave trade between mainly southern Bengal and the Cape in the Republic of South Africa. This migration took place between roughly the 1650s and about the middle of the nineteenth century when the slave trade was finally abolished. The book offers a short account of the condition in which the Bengali slaves found themselves and in the Cape peninsular society following their dispersal during these early times. It highlights new social formations in the Cape society, especially among the Coloured in South Africa"--Back cover.
Introduction -- Export of Bengali slaves to the Cape -- Early beginning -- Bengali slaves? Who were they? -- Bengali slave owners -- Slave trade modalities -- Preferences for slaves -- Demographic profile -- Conditions in which Bengali slaves lived and worked -- Common slave culture? -- Protest, resistance, and revolt -- Incorporation of Bengali slaves into mainstream Cape society -- Malays vs. Indians as the core Coloured group -- Conclusion -- Sources -- End notes -- Appendices.
Includes bibliographical references and index.
ENH
Book Finder International
Keywords: Slavery -- South Africa -- Cape of Good Hope; Enslaved persons -- India -- Bengal -- History; Enslaved persons -- South Africa -- Cape of Good Hope -- Biography; Bengal (India). -- History; Cape of Good Hope (South Africa) -- History